Review Article : Investigasi Forensik Email dengan Berbagai Pendekatan dan Tools - Imam Riadi; Rusydi Umar; Mustafa Mustafa (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
Computer forensic science is a relatively new science and not even widely known among the public. Unlike the real world, crime in the world of computers and the internet has so many variations, one of which is forgery or spam email, where spam e-mail can be a means of transporting malicious content on a network. The problem that arises at this time is that very little research is conducted in the case of forensic investigations in the face of crime in the cyber world, especially in the spam e-mail. The method used is observation of literature, in this case in the form of original articles that analyze about crimes that use email, including the flow and tools used. The results obtained in this article review are that each investigation and tools approach has advantages and disadvantages of each, so that users can adjust to their needs.